(untitled) (International Journal of Pharmaceutical Sciences and Drug Research, 2021)
The current investigation’s objective was to study the physicochemical characterization of Diclofenac and Rasagiline salts and its relationship to the development of sublingual drug delivery systems. The selected salts of Diclofenac and Rasagiline were evaluated for crystallinity (XRD), thermogravimetric analysis (TGA), differential scanning calorimetry (DSC), Fourier transform infrared spectroscopy (FTIR), solubility, in vitro dissolution and taste evaluation using e-tongue. The physicochemical characterization of Diclofenac salts demonstrated that potassium, epolamine and sodium salts of diclofenac showed similar results. Diclofenac free acid is not suitable for this route of administration as solubility was very less in sacrospinous fixation (SSF) media. Rasagiline mesylate was found more soluble and stable compared to hemitartrate salt. But being a low dose molecule, the impact of dose on the solubility or dissolution was considered negligible. Hence hemitartrate salt was selected as an alternate salt form for development of new sublingual administration.